Strategi Pembelajaran Berbasis ICT Digital-Creative Pedagogy terhadap Peningkatan Keterampilan Berpikir Kritis dan Kreatif Mahasiswa Calon Guru SD pada Materi Pencemaran Lingkungan Mata Kuliah Praktikum IPA - Dede Sustri; Muhammad Gumilar; saryati purwanigara (LP2M UIN Ambon, 2026)
This study aims to examine the effectiveness of the ICT-based Di-Cre-P (Digital-Creative Pedagogy) learning strategy in enhancing students' critical and creative thinking skills on Environmental Pollution topics. The research method used was a quasi-experimental approach with a Non-equivalent Control Group Design. The sample consisted of two classes of elementary school teacher education students selected through purposive sampling. Research instruments included critical thinking essay tests and creative media product assessment rubrics. Data were analyzed using N-Gain scores and Independent Sample T-tests. The results showed a significant increase in the experimental class with an N-Gain score of 0.79 (high category), compared to the control class at 0.31 (low category). The t-test results showed a significance value of 0.000 < 0.05, meaning the Di-Cre-P strategy is significantly effective in improving students' analytical and innovative abilities. The novelty of this research lies in the integration of the student's role as a digital content creator, training both pedagogical and science content aspects simultaneously. It is concluded that the Di-Cre-P strategy is capable of preparing adaptive pre-service teachers ready to support the Pancasila Student Profile in the digital era.students' critical thinking skills. Students' active involvement in identifying problems, analyzing information, and formulating solutions based on scientific evidence trains students to think logically, reflectively, and systematically. The problem-solving model is effectively used as a biology learning strategy to develop students' critical thinking skills.